Evaluating the Long-Term Trend and Management of a Globally Important Loggerhead Population Nesting on Masirah Island, Sultanate of Oman - Willson, Andrew; Witherington, Blair; Baldwin, Robert; Tiwari, Manjula; Al Sariri, Thuraya; Al Kiyumi, Ali; Al Harthi, Suaad; Willson, Maïa Sarrouf; Al Bulushi, Asma; Al Farsi, Ghasi; Al Humaidy, Juma; Al Araimi, Juma; et al. (Frontiers in Marine Science, 2020)
Nest count surveys provide an important means for tracking trends in marine turtle populations. In 2015 the IUCN Red List global status review changed the loggerhead turtle (Carretta caretta) from Endangered to Vulnerable status, and, with a revised regional management unit (RMU) assessment system in place, concluded that the Northwest Indian Ocean loggerhead turtle RMU was Critically Endangered (CR). We analyzed annual time series nest count survey data between 1978 and 2016 to evaluate population trend and characterize the existing spatial and temporal attributes of a globally significant rookery on Masirah Island, Oman. A two-point trend assessment using a subset of historical data (1985-1996) combined with recent data (2008-2016) on a representative, 9-km section of index beaches revealed a change from 584 tracks-1 km-1 season-1 (SD = 109.5) to 122.43 tracks-1 km-1 season-1 (SD = 37.3), representing a statistically significant 79% decline. Comparative data were tested for spatial and temporal conformity, and the influence of other parameters on the trend result were considered, such as nesting success ratios and spatial shifts in density. Our analyses confirm that the decline occurred within a single loggerhead generation. Mean multiyear nest counts from recent surveys provides an estimate of 55,202 nests year-1 (SD=16,814, CI 0.95 53,326- 57,078) across 83 km of nesting beach. Considering recent clutch frequency estimates the mean number of nesting loggerheads per year is estimated between 10,223 (CI 0.95 9,875- 10,570) and 11,500 (CI 0.95 11,109- 11,891). The Northwest Indian Ocean RMU is thought to represent 35% of the global nesting population. Recognizing a pressing need to address the decline in this population we identify potential threats on nesting beaches and at sea which point towards priority actions for conservation of this CR RMU.